Comprehensive optimisation and practical design of LCL filter for shunt active power filter. (1st January 2014) - Deng, Xiangtian; Yuan, Rongxiang; Xiao, Zhenfeng; Yan, Pan
Shunt Active Power Filter (SAPF) can be applied to compensate for existing source-type current harmonics. However, high-precision compensation is difficult because harmonic current has a large variation and the current loop has a steady-state error. A design method for a new practical LCL filter based on SAPF is proposed in this paper. A harmonic model of the LCL filter is built based on SAPF application. The changing relationship between the parameters of the filter and harmonic frequency is then examined. The suitable values for the parameters are determined based on the precondition of having a split ratio of 1, the limit scope of LCL resonance frequency and the ratio of the capacitance branch's impedance parameter in combination with the relationship curve of the inductance parameter ratio and harmonic frequency as well as the respective requirements of the LCL regarding the attenuating properties of lowand high-frequency bands. Finally, the validity and feasibility of the design method are verified by conducting an experiment with SAPF's industrial prototype.